Country of Origin and Purchase Decision: Examining The Moderating Effects of Brand Value, Service Quality, and Promotion in The Indonesian Footwear Market - Petrus Pardede; Yohanes Lubis; Kendy Prayogo; Bambang Suwarno; Shaista Noor (International Journal of Science and Environment (IJSE), 2026)
Country of origin has been widely acknowledged as an important extrinsic cue influencing consumer purchase decisions; however, empirical evidence explaining its indirect mechanisms through marketing-related constructs in local brand contexts remains limited. This study aims to examine the effect of country of origin on purchase decisions, incorporating brand equity, service quality, and promotion as explanatory constructs within a structural model. A quantitative research design was employed using survey data collected from 384 university students in Medan, Indonesia, who had purchased and used Ventela shoes. Data were analyzed using Structural Equation Modeling–Partial Least Squares. The results demonstrate that the country of origin has a significant positive effect on purchase decisions. In addition, the country of origin significantly influences brand equity, service quality, and promotion, which in turn positively affect purchase decisions. The structural model indicates that brand equity, service quality, and promotion play important mediating roles in strengthening the relationship between country of origin and purchase decisions. Overall, the model explains a substantial proportion of variance in purchase decisions, highlighting the robustness of the proposed framework. This study extends the country-of-origin literature by providing empirical evidence on the indirect pathways through which country-of-origin perceptions shape consumer behavior toward local footwear brands in emerging markets. In practice, the findings offer strategic insights for local brand managers on leveraging brand equity, service quality, and promotional activities to enhance consumer purchase decisions.